Wild Mouse Gut Microbiota Promotes Host Fitness and Improves Disease Resistance - Rosshart, Stephan P.; Vassallo, Brian G.; Angeletti, Davide; Hutchinson, Diane S.; Morgan, Andrew P.; Takeda, Kazuyo; Hickman, Heather D.; Mcculloch, John A.; Badger, Jonathan H.; Ajami, Nadim J.; Trinchieri, Giorgio; De Villena, Fernando Pardo-Manuel; et al. (Cell, 2017)
Laboratory mice, while paramount for understanding basic biological phenomena, are limited in modeling complex diseases of humans and other free-living mammals. Because the microbiome is a major factor in mammalian physiology, we aimed to identify a naturally evolved reference microbiome to better recapitulate physiological phenomena relevant in the natural world outside the laboratory. Among 21 distinct mouse populations worldwide, we identified a closely related wild relative to standard laboratory mouse strains. Its bacterial gut microbiome differed significantly from its laboratory mouse counterpart and was transferred to and maintained in laboratory mice over several generations. Laboratory mice reconstituted with natural microbiota exhibited reduced inflammation and increased survival following influenza virus infection and improved resistance against mutagen/inflammation-induced colorectal tumorigenesis. By demonstrating the host fitness-promoting traits of natural microbiota, our findings should enable the discovery of protective mechanisms relevant in the natural world and improve the modeling of complex diseases of free-living mammals. Video Abstract Characterization of a wild mice reference microbiome opens a window of opportunity to understand how the gut microbiota affects aspects of host physiology that are important in the natural world outside the laboratory.
CRIS-Team Scopus Importer:2022-12-14
Keywords: bacteria; colorectal cancer; cytokine; gut; inflammation; influenza; innate; microbiome; virus; wild mouse